Customary Law and the Challenges of Modern Investment: Strategies for Maintaining a Balance between Traditional Values and Economic Growth - Pramidazzura Alifa Rifqi (PT. Anagata Sembagi Education, 2026)
This article examines the challenges posed by modern investment to customary law and proposes legal strategies to maintain a balance between traditional values and economic growth. While investment is promoted as a key driver of development, its implementation in customary territories often generates normative conflicts arising from divergent conceptions of land, consent, and economic relations. This study identifies three central legal issues: normative ambiguity regarding the position of customary law in investment governance, a legal vacuum in the binding recognition of customary consent, and conflicts of norms between market-oriented investment regimes and communal legal systems. Employing a normative juridical method with statute, conceptual, and case approaches, the article analyzes constitutional recognition of indigenous rights, investment-related legal frameworks, and comparative doctrinal perspectives. The analysis demonstrates that customary law should not be treated as an obstacle to investment, but as a normative constraint and enabler that can enhance social legitimacy, reduce conflict, and support sustainable economic growth. The article argues that investment governance which marginalizes customary norms ultimately undermines legal certainty and long-term economic stability. It proposes prescriptive legal strategies, including strengthening the legal status of customary consent, integrating customary norms into impact assessments, institutional coordination with customary authorities, and pluralistic judicial interpretation. Integrating customary law into investment regulation is essential to reconcile economic development with social justice and legal coherence.